PERSEPSI DAN PREFERENSI WARNA DALAM LANSKAP - Wasissa Titi; Andi Gunawan (Jurnal Lanskap Indonesia, 2011)
Color is one of important elements in our life, everything will be easier to seeing something with it. Color is element which make power of attraction in design, because color have emotional component that emerge when people see it. A beautiful landscape also have element of interesting colors. For this reason, people can enjoy all element in landscape.Every people has different perception and preference when they see color. As each colors have different characteristic. They influence the preference for landscape. Research has shown that personal preference is not only influenced by color. Landscapewill be more interesting when is the embedded color is in harmonious combination with other elements.